Moving the Indonesian capital city and social Implications for Sabah - Amrullah Maraining; Ramli Dollah (Borneo International Conference on Islamic Higher Education, 2023)
Malaysia-Indonesia is one of the most important countries in the world. Malaysia is also the second most important country in Indonesia, and Malaysia is the third most important. Indonesia is a country with the largest number of people living in Malaysia. Malaysia and Indonesia are a part of the world, and Indonesia is the second largest country in terms of the total number of Malaysians living in Indonesia. Malaysia is the fourth largest country, with a population of 1.9 million people. Malaysia has the highest number of residents living in Southeast Asia and the third largest in Southeast Asian countries